Cloud security : a comprehensive guide to secure cloud computing - Krutz, Ronald L., 1938-; Vines, Russell Dean, 1952- (New Delhi Wiley, 2010)
This book covers cloud computing fundamentals, architectures, service delivery approaches, deployment models, software as a service, platform as a service, and security governance.
Cloud computing fundamentals -- Cloud computing architecture -- Cloud computing security fundamentals -- Cloud computing risk issues -- Cloud computing security challenges -- Cloud computing security architecture -- Cloud computing life cycle issues -- Useful next steps and approaches.
Includes bibliographical references and index.
Keywords: Cloud computing -- Security measures; Computer security; Data processing; Computer security